Aerogel-Based TiO2 Stable Inks for Direct Inkjet Printing of Nanostructured Layers - Aline M. Barreiro; Geneviève K. Pinheiro; Bruno N. Wesling; Daliana Müller; Letícia T. Scarabelot; Luciana V. de Souza; Dachamir Hotza; Carlos R. Rambo (Advances in Materials Science and Engineering)
Inkjet printing presents a high potential for cost reduction of electronic devices manufacturing due to the capacity to deposit materials with high precision, less material waste, and large-scale production through the roll-to-roll printing processes. In this work, a nanostructured TiO2 ink was developed using TiO2 aerogel and an alkaline aqueous solution, which resulted in a very stable suspension. A high-intensity ultrasonic mixer was used to fragment and disperse TiO2 aerogels producing suspensions with particles smaller than 200 nm, which are suitable for the inkjet printing process. For the development of the ink, the viscosity and surface tension were adjusted by using glycerol and a surfactant (Triton X-100). The influence of those components on the properties of the ink was evaluated for different concentrations. After formulation of the inks, the printing parameters were adjusted to optimize the process. Films with high surface area and less than 100 nm grain size were successfully produced. Electrical measurements revealed a resistive-like behavior with the sheet resistance increasing with number of printed layers.